2022
DOI: 10.3389/fendo.2022.874849
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Icariin on Modulating Gut Microbiota and Regulating Metabolite Alterations to Prevent Bone Loss in Ovariectomized Rat Model

Abstract: Postmenopausal osteoporosis (PMOP) is an estrogen deficiency-induced bone loss, which has been shown an association with an altered gut microbiota (GM). Gut microbiota-bone axis has been recognized as a crucial mediator for bone homeostasis. Icariin (ICA) is an effective agent to delay bone loss by regulating the bone homeostasis. Thus, we hypothesize that ICA can prevent bone loss by modulating GM and regulating metabolite alterations. The effects of ICA on bone metabolism improvement in ovariectomized (OVX) … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 74 publications
4
11
0
Order By: Relevance
“…Several studies have reported that Bilophila and Ruminococcus are closely related to cholesterol, which is strongly associated with bone health. , High cholesterol increases osteoclast activity and decreases osteoblast function, especially in bone residential cells . Meanwhile, it has been reported that Ruminococcus correlates with serum indexes of bone homeostasis and inflammation while Ruminococcus protects intestinal mucus from degradation against the entry of harmful substances into the blood in ethanol-induced osteoporosis . We found that the relative abundance of Ruminococcus correlated negatively with TC concentration, which was significantly decreased in our study.…”
Section: Discussionsupporting
confidence: 53%
See 1 more Smart Citation
“…Several studies have reported that Bilophila and Ruminococcus are closely related to cholesterol, which is strongly associated with bone health. , High cholesterol increases osteoclast activity and decreases osteoblast function, especially in bone residential cells . Meanwhile, it has been reported that Ruminococcus correlates with serum indexes of bone homeostasis and inflammation while Ruminococcus protects intestinal mucus from degradation against the entry of harmful substances into the blood in ethanol-induced osteoporosis . We found that the relative abundance of Ruminococcus correlated negatively with TC concentration, which was significantly decreased in our study.…”
Section: Discussionsupporting
confidence: 53%
“…35 Meanwhile, it has been reported that Ruminococcus correlates with serum indexes of bone homeostasis and inflammation while Ruminococcus protects intestinal mucus from degradation against the entry of harmful substances into the blood in ethanol-induced osteoporosis. 37 We found that the relative abundance of Ruminococcus correlated negatively with TC concentration, which was significantly decreased in our study. In contrast, bone parameters are positively correlated with the relative abundance of Ruminococcus.…”
Section: Discussionsupporting
confidence: 42%
“…Estrogen deficiency can stimulate RAKNL expression and extend osteoclasts' lifespans while shortening osteoblasts'. 30 Enrichment analysis of pathways containing 25 differential metabolites revealed five pathways: unsaturated fatty acid biosynthesis, arachidonic acid metabolism, glycerophospholipid metabolism, steroid biosynthesis pathway, and primary bile acid biosynthesis. Only the first two pathways had p -values <0.05 with −log ( p ) > 2; consequently, arachidonic acid metabolism and unsaturated fatty acid biosynthesis were selected for analysis.…”
Section: Resultsmentioning
confidence: 99%
“…Notably, previous research demonstrated that Allobaculum may be a key microbial community that drives the metabolism of bile acid, amino acid, and fatty acid, thereby improving postmenopausal OP. 47 In addition, Zhou et al reported that Allobaculum is a specific bacteria associated with calcium absorption in osteoporotic rats, which may participate in improved BMD and bone microarchitecture. 48 To ulteriorly identify the specific microbial taxa that exhibited the largest differences between OVX + NS and OVX + MLT groups and were associated with MLT treatment, we performed linear discriminant analysis Effect Size (LEfSe) and Cladogram (based on maximum relative abundance difference in each level) analyses, which determined 8 strains of bacteria enriched in MLT-treated mice, while seven strains were enriched in OVX + NS mice (Figure 6I,J).…”
Section: Treatment With Mlt Reshaped the Combination And Structure Of...mentioning
confidence: 99%